Left ventricular adaptation following orthotopic heart transplantation in children: A speckle tracking echocardiographic imaging study. Issue 8 (15th July 2019) - Sahewalla, Rini; Sehgal, Swati; Blake, Jennifer; Aggarwal, Sanjeev
Abstract: Background: Evolution of left ventricle (LV) function in the pediatric OHT population has not been well described. Our hypothesis was that, in children following OHT without any rejection, there would be progressive normalization of LV size and function over 2 years. Methods: LV function was evaluated using STE and conventional echo parameters at five time points in pediatric OHT patients without any rejection in the first 2 years following OHT and normal controls. LV global peak systolic longitudinal strain (LVPLS) and strain rate, LV peak systolic radial and circumferential strain (LVRS and LVCS), and strain rate were analyzed. Results: We had twenty two patients with median age at OHT of 1.27 years ( IQR 0.19, 5.6 years). The LVPLS (mean ± SD) was abnormal in the post‐OHT echocardiograms at 1 week (−12.4 ± 3.7) and 1 month (−13.9 ± 3.7) and significantly improved at 6 months (−15.8 ± 3.2), 1 year (−15.7 ± 3.1), and 2 years (−17.8 ± 2.8). However, LVPLS remained below the normal group even at 2 years following OHT (−21.3 ± 1.76). Conclusion: In children following OHT, despite the absence of rejection, strain values are significantly impaired in the initial months, improve progressively over the first 2 years but remain abnormal compared with healthy controls.